1970
DOI: 10.3329/ujzru.v25i0.325
|View full text |Cite
|
Sign up to set email alerts
|

Physio-chemical conditions and plankton population of two fishponds in Khulna

Abstract: Sixteen physico-chemical variables, and the diversity and abundance of phyto- and zooplankton of two fishponds in Khulna University Campus have been studied during October 2003 and September 2004. A total of 25 phytoplankton genera, 7 belonging to Cyanophyceae, 7 to Chlorophyceae, 8 to Bacillario-phyceae and 3 to Euglenophyceae, and 18 zooplankton genera, 4 belonging to Copepoda, 7 to Cladocera and 7 to Rotifera, were recorded. Both ponds were permanently alkaline in nature. The values of TDS, BOD and phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

1970
1970
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 5 publications
4
15
0
1
Order By: Relevance
“…Although chlorophyll pigment was not measured, the greenish color of the pond water suggested that the particulate matter mainly consisted of phytoplankton community. Chowdhury and Mamun (2006) reported high abundance of Cyanophyceae in two fishponds in Khulna during dry season. Affan et al (2005) reported that chlorophyll a concentration in a pond of central Bangladesh became higher in March (dry season) than the concentration in September (wet season).…”
Section: Changes In Pond Size and Water Quality During The Dry Seasonmentioning
confidence: 99%
See 2 more Smart Citations
“…Although chlorophyll pigment was not measured, the greenish color of the pond water suggested that the particulate matter mainly consisted of phytoplankton community. Chowdhury and Mamun (2006) reported high abundance of Cyanophyceae in two fishponds in Khulna during dry season. Affan et al (2005) reported that chlorophyll a concentration in a pond of central Bangladesh became higher in March (dry season) than the concentration in September (wet season).…”
Section: Changes In Pond Size and Water Quality During The Dry Seasonmentioning
confidence: 99%
“…1)). A significant number of natural wetlands and artificial ponds cover the area (Chowdhury and Mamun, 2006). The ponds in the villages are used for many purposes: rural domestic uses including dish washing, laundry, bathing and cooking (Sultana and Crow, 2000), wastewater storage use, agriculture use (paddy fields) especially in Rupsa and Mollahat and fishery use (prawns and fish) in Fakirhat.…”
Section: Surveyed Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The main foods of rui, catla and catla-rui hybrid were plankton in origin (Mozumder and Naser 2009). Several investigations have been made on the community structure of zooplankton in inland aquatic ecosystems of Bangladesh (Habib et al 1984, Patra and Azadi 1987, Chowdhury et al 1989, Kabir et al 1996, Bhuiyan and Nessa 1998, Hasan et al 2001, Chowdhury and Mamun 2006, Islam 2007, Kabir and Naser 2008, Ahmed et al 2011. It has recently been shown that the aquatic and freeliving pseudopod, Acanthamoeba castellanii is not a predator to V. cholerae O139 rather the bacterium has shown an intracellular compatibility with this host.…”
Section: Introductionmentioning
confidence: 99%
“…Homyra & Naz (2005) studied limnology of an artificial lake of Rajshahi. Chowdhury & Mamun (2006) worked on physico-chemical conditions and plankton population of two fish ponds in Khulna. Many researchers worked on the percentage composition, seasonal variation and occurrence of freshwater zooplankton, but little or no information is available on the abundance of zooplankton in culture and non-culture pond in relation to water quality parameters.…”
Section: Introductionmentioning
confidence: 99%